PROBLEMATIKA K13 DALAM PEMBELAJARAN PAI - Hidayatulloh, Arif; Anam, Wahidul; Fanani, Moh. Zainal (Institut Agama Islam Negeri Kediri, 2017)
Abstract: The 2013 curriculum, aimed at encouraging learners, is better able to observe, ask, reason, and communicate (present), what they gain or know after receiving learning materials. Research focus: 1) How is the implementation of Curriculum 2013 in Kediri City? and 2) How is the Problem faced by Islamic Religious Education Teachers (PAI) in Implementing the 2013 Curriculum in Kediri City? The results of this study revealed that: 1) Implementation of Curriculum 2013 in Kediri City has not run maximally there are still shortcomings that must be improved for example, mentoring in implementation is very less. 2) Problematic Teachers PAI, among others, have difficulty in implementing learning, due to lack of understanding of teachers about the Curriculum 2013 with the concept of learning Curriculum 2013, the delay of procurement training for teachers, especially teachers PAI about the curriculum 2013, and so on Insufficient facilities and infrastructure in supporting the implementation of Curriculum 2013 in some of the existing in Kediri, thus hindering the implementation of the applied curriculum. Abstrak: Kurikulum 2013, bertujuan mendorong peserta didik, mampu lebih baik dalam melakukan observasi, bertanya, bernalar, dan mengkomunikasikan (mempresentasikan), apa yang mereka peroleh atau mereka ketahui setelah menerima materi pembelajaran. Fokus penelitian: 1) Bagaimana implementasi Kurikulum 2013 di Kota Kediri? dan 2) Bagaimana Problematika yang dihadapi Guru Pendidikan Agama Islam (PAI) dalam Mengimplementasikan Kurikulum 2013 di Kota Kediri ? Hasil penelitian ini mengungkapkan bahwa: 1) Implementasi Kurikulum 2013 di Kota Kediri belum berjalan dengan maksimal masih ada kekurangan-kekurangan yang harus di perbaiki contohnya saja pendampingan dalam implementasi itu sangat kurang. 2) Problematika Guru PAI antara lain mengalami kesulitan dalam melaksanakan pembelajaran, karena kurangnya pemahaman guru tentang Kurikulum 2013 dengan konsep pembelajaran Kurikulum 2013, keterlambatan pengadaan pelatihan bagi guru-guru, khususnya guru PAI tentang kurikulum 2013, dan sebagainya terakhir Sarana dan prasarana yang kurang memadai dalam menunjang pelaksanaan Kurikulum 2013 di beberapa yang ada di Kota Kediri, sehingga menghambat pelaksanaan kurikulum yang diterapkan.